Has the green total factor productivity increased in the early stage of the establishment of smart city - An-wei Wan; Wei Cui (PLoS ONE, 2025)
In the context of global climate change, green development has become the main goal of smart city construction. Most existing research suggests that smart cities will enhance the level of the green total factor productivity (GTFP) in cities. However, this study found that smart cities will reduce the level of green total factor production in the short term and increase it in the long term. Based on this, this article selects three batches of smart cities in China from 2013 to 2019, and uses the Malmquist index model, common frontier function, and panel data method to analyze the GTFP model in the early stage of smart city construction in China. The study found that: (1) the GTFP of the three batches of smart cities in the early stage of construction was less than 1 and showed a downward trend, indicating that smart cities will reduce the GTFP level of cities in the short term. (2) Technical efficiency is the main reason for the decline of GTFP in the early stage of smart city construction and the rise of GTFP in the medium and long term. Specifically, there is a U-shaped relationship between the technological efficiency of smart cities and their GTFP. For every 1% increase in technical efficiency in the later stages of smart cities, GTFP increases by 47.3%. (3) The GTFP in the process of smart city construction shows a trend of decreasing in the early stage and increasing in the middle and later stages. The GTFP level in the later stage of smart cities is greater than 1 and shows a fluctuating upward trend, indicating that smart cities will improve the city’s GTFP level in the long run. In view of this, we should attach importance to ecological protection in the early stage of smart city construction and take effective measures to reduce carbon emissions during this period. During this period, policies such as taxation can be implemented to encourage companies to adopt cleaner production technologies, strengthen the exchange of green technologies between cities, accelerate the flow of green knowledge, reduce redundant construction of information infrastructure, and thus minimize the decline in GTFP in the early stages of smart city construction. This study provides policy recommendations and decision-making references for further promoting the construction of new green and smart cities worldwide.